Rural Bankers Workshop, 1960n- a summary report. - Rural Bankers Association of the Philippines; Central Bank of the Philippines. Department of Rural Banks; Rural Bankers Workshop ([Manila] Dept. of Rural Banks, Central Bank of the Philippines)
Annual.
"Held in conjunction with the 7thn-
Annual Convention of Rural Bankers."
Keywords: Banks and banking -- Philippines; Bankers -- Philippines